2022
DOI: 10.29228/jrp.175
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and in vitro mutagenic, antioxidant and anti-inflammatory activities of Lavandula angustifolia Mill. essential oil from Turkey

Abstract: The essential oil obtained from Lavandula angustifolia Mill. (Lavander) has many pharmacological effects, including antioxidant, antifungal, antibacterial and carminative effects. Lavandula angustifolia essential oil (LEO) contains monoterpene compounds, mainly linalool and linalyl acetate and various phenolic acids such as caffeic acid, vanillic acid, ferulic acid and chlorogenic acid. The hydrodistillation of the aerial parts of L. angustifolia produced a pale yellow oil. Gas chromatography-Gas chromatograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Linalyl acetate ( 3b , Figure 3 ) has been well documented to have favorable bioactivities. Anticancer properties have been associated with essential oils from Lavandula angustifolia, Lavandula officinalis, Lavandula latifolia , and bergamot [ 40 , 41 , 42 , 43 , 44 ], all of which contain linalyl acetate in concentrations as high as 44%. A study conducted on the lavender essential oils from Lavandula angustifolia demonstrated an IC 50 values of 0.36% ( v / v ) against HaCaT cell line in an MTT assay [ 43 ].…”
Section: Biological Activities Of Monoterpenesmentioning
confidence: 99%
“…Linalyl acetate ( 3b , Figure 3 ) has been well documented to have favorable bioactivities. Anticancer properties have been associated with essential oils from Lavandula angustifolia, Lavandula officinalis, Lavandula latifolia , and bergamot [ 40 , 41 , 42 , 43 , 44 ], all of which contain linalyl acetate in concentrations as high as 44%. A study conducted on the lavender essential oils from Lavandula angustifolia demonstrated an IC 50 values of 0.36% ( v / v ) against HaCaT cell line in an MTT assay [ 43 ].…”
Section: Biological Activities Of Monoterpenesmentioning
confidence: 99%
“…Thus, more investigations would be suitable for wide lavender screening in all regions of Morocco. Omurtag Özgen et al [32], who examined the chemical composition of Lavandula angustifolia EO from Konya, Turkey, also yielded a different result as they found 28 compounds with a predominance of linalool (35.91%), 4-terpineol (6.10%), alpha-terpineol (4.49%) and lavandulol (2.49%) [28]. (4.4%) [27].…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Te EO was found to exhibit insecticidal activity and increase the percent repellency against insects [18,19]. Additionally, lavender essential oil has been shown to have antioxidant, antimicrobial, and antifungal properties [20,21]. Besides, geranium EO has been studied about various insects; e.g., it showed a repellent efect against adult fies, specifcally Musca domestica and Lucilia cuprina.…”
Section: Introductionmentioning
confidence: 99%